Medical Students’ Attitudes toward Abortion Education: Malaysian Perspective - Tey, Nai-peng (Public Library of Science, 2012)
BACKGROUND: Abortion is a serious public health issue, and it poses high risks to the health and life of women. Yet safe abortion services are not readily available because few doctors are trained to provide such services. Many doctors are unaware of laws pertaining to abortion. This article reports survey findings on Malaysian medical students’ attitudes toward abortion education and presents a case for including abortion education in medical schools. METHODS AND RESULTS: A survey on knowledge of and attitudes toward abortion among medical students was conducted in two public universities and a private university in Malaysia in 2011. A total of 1,060 students returned the completed questionnaires. The survey covered about 90% of medical students in Years 1, 3, and 5 in the three universities. About 90% of the students wanted more training on the general knowledge and legal aspects of abortion, and pre-and post-abortion counseling. Overall, 75.9% and 81.0% of the students were in favor of including in medical education the training on surgical abortion techniques and medical abortion, respectively. Only 2.4% and 1.7% were opposed to the inclusion of training of these two methods in the curriculum. The remaining respondents were neutral in their stand. Desire for more abortion education was associated with students’ pro-choice index, their intention to provide abortion services in future practice, and year of study. However, students’ attitudes toward abortion were not significantly associated with gender, type of university, or ethnicity. CONCLUSIONS: Most students wanted more training on abortion. Some students also expressed their intention to provide abortion counseling and services in their future practice. Their desire for more training on abortion should be taken into account in the new curriculum. Abortion education is an important step towards making available safe abortion services to enable women to exercise their reproductive rights.